Symbolic Resistance of the Subaltern in Palestine in the Novel Rijāl fī Asy-Syams by Ghassan Kanafani: Postcolonial Approach of Gayatri C. Spivak: Al-Muqāwamah ar-Ramziyyah li al-Fa’ah al-Muḥtammashah fī Filasṭīn fī Riwāyat Rijāl fī asy-Syams li Ghassān Kanafānī: al-Manhaj Mā Ba‘da al-Isti‘mār li Gayatri Spivak - Muhammad Nazar; Sindy Febrianisa; Siti Karomah (An-Nahdah Al-'Arabiyah, 2026)
This study aims to identify the forms of colonial domination over the subaltern in Palestine and to reveal the symbolic resistance of the subaltern against colonialism in the novel Rijāl Fī Asy-Syams by Ghassan Kanafani. The central issue in the novel concerns the silencing of subaltern voices by the upper-class society in Palestine. This research is a library research employing a qualitative approach. The study adopts Gayatri C. Spivak’s postcolonial theory as its analytical framework. The data consist of words, phrases, and sentences related to symbolic resistance found in the novel Rijāl Fī Asy-Syams. Data collection techniques include reading and categorizing data in accordance with the research focus. Data analysis was conducted through reading, describing, interpreting, and drawing conclusions. The findings of this study reveal seven forms of domination carried out by the upper class, including those in power in Palestine. These are economic, ideological, religious, social, gender-based, capitalist, and political domination.   يهدف هذا البحث إلى اكتشاف أشكال هيمنة الاستعمار على الفئات الدنيا (السوبالترن) في فلسطين، وكشف أشكال المقاومة الرمزية التي تقوم بها هذه الفئات ضد الاستعمار في رواية "رجال في الشمس" لغسان كنفاني. تتعلق المشكلة المطروحة في الرواية بعدم سماع أصوات الفئات الدنيا من قبل الطبقات العليا في المجتمع الفلسطيني. نوع هذا البحث هو بحث مكتبي (library research) باستخدام المنهج النوعي. ويعتمد هذا البحث على مقاربة ما بعد الاستعمار التي طرحتها غاياتري تشاكرافورتي سبيفاك. أما بيانات هذا البحث فتتمثل في الكلمات والعبارات والجمل المتعلقة بالمقاومة الرمزية الواردة في رواية "رجال في الشمس". أما طريقة جمع البيانات فتعتمد على القراءة وتصنيف البيانات وفقاً لموضوع البحث. وتم تحليل البيانات من خلال القراءة، والوصف، والتفسير، ثم استنتاج النتائج. وصلت نتائج هذا البحث إلى وجود سبعة أشكال من الهيمنة تمارسها الطبقات العليا في المجتمع، بما في ذلك الحكّام في فلسطين، وهي: الهيمنة الاقتصادية، والأيديولوجية، والدينية، والاجتماعية، والجندرية، والرأسمالية، والسياسية.   Penelitian ini bertujuan untuk menemukan bentuk dominasi kolonialisme terhadap subaltern di Palestina dan mengungkapkan resistensi simbolik subaltern terhadap kolonialisme dalam Novel Rijāl Fī Asy-Syams karya Ghassan Kanafani. Permasalahan yang terjadi dalam Novel tersebut berkaitan dengan tidak didengarnya suara-suara subaltern oleh masyarakat kalangan atas di Palestina. Jenis penelitian ini adalah library research dengan pendekatan kualitatif. Penelitian ini menggunakan pendekatan Poskolonial Gayatri C. Spivak. Data dalam penellitian yaitu kata, frasa serta kalimat yang berkaitan dengan resistensi simbolik yang terdapat dalam novel Rijāl Fī Asy-Syams karya Ghassan Kanafani. Teknik pengumpulan data yaitu membaca dan mengelompokkan data sesuai objek penelitian. Teknik analisis data dengan membaca, mendeskripsikan, menafsirkan, dan menarik kesimpulan. Hasil penelitian ini menemukan adanya tujuh bentuk dominasi yang dilakukan oleh masyarakat kalangan atas, termasuk juga para penguasa di Palestina, yaitu dominasi ekonomi, ideologi, agama, sosial, gender, kapitalis, dan politik.